1986
DOI: 10.1093/mutage/1.3.179
|View full text |Cite
|
Sign up to set email alerts
|

Genetic toxicology of flavonoids: the role of metabolic conditions in the induction of reverse mutation, SOS functions and sisterchromatid exchanges

Abstract: Glycosides of flavonols such as quercetin, are found in the edible portions of most food vegetables. Flavonols present in plants as glycosides can be freed during fermentation. We have compared the DNA-damaging activity of quercetin, rutin (3-o-rutinoside of quercetin) and a fermented flavonoid-containing beverage, red wine, for different genetic end-points under different metabolic conditions. The genotoxicity of quercetin, rutin and commercial red wine has been studied for the induction of: (i) reverse mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 26 publications
1
19
1
Order By: Relevance
“…Moreover, In Escherichia coli, quercetin has been shown to induce SOS activity, reverse mutations, and DNA single strand breaks with or without metabolic activation [46]- [49]. These positive mutagenic and genotoxic responses in bacterial test systems have been confirmed in eukaryotic cells, including yeast [50] and mammalian cells included mouse, hamster, rat and human [51]- [55], in which sister chromatid exchanges, chromosomal aberrations, unscheduled DNA synthesis (UDS), and micronucleus formation are among some of the endpoints evaluated. However, in a study for a 2-year rodent carcinogenicity bioassay conducted by the National Toxicology Program (NTP), these genotoxic effects have not confirmed suggesting the safety of quercetin for oral consumption in humans [52] [56] [57].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, In Escherichia coli, quercetin has been shown to induce SOS activity, reverse mutations, and DNA single strand breaks with or without metabolic activation [46]- [49]. These positive mutagenic and genotoxic responses in bacterial test systems have been confirmed in eukaryotic cells, including yeast [50] and mammalian cells included mouse, hamster, rat and human [51]- [55], in which sister chromatid exchanges, chromosomal aberrations, unscheduled DNA synthesis (UDS), and micronucleus formation are among some of the endpoints evaluated. However, in a study for a 2-year rodent carcinogenicity bioassay conducted by the National Toxicology Program (NTP), these genotoxic effects have not confirmed suggesting the safety of quercetin for oral consumption in humans [52] [56] [57].…”
Section: Introductionmentioning
confidence: 99%
“…The induction of SOS activity, reverse mutation and DNA single strand breaks in the presence or absence of metabolic activation has been observed in Escherichia coli (Hardigree & Epler, 1978;Llagostera et al, 1987;Rueff et al, 1986). Similarly, mutagenic and genotoxic activities of quercetin has been confirmed in eukaryotic cells (Hardigree & Epler, 1978) and mammalian cells (Yoshida et al, 1980;Van der Hoeven et al, 1984;Rueff et al, 1986;Kubiak & Rudek, 1990;Gasper et al, 1994;Caria et al, 1995). In these various studies, sister chromatid exchange, chromosomal aberrations, unscheduled DNA synthesis (UDS) and micronucleus formation were endpoints evaluated.…”
Section: ) Effectsmechanism Of Actionmentioning
confidence: 89%
“…Several studies confirmed and extended the initial observations of Bjeldanes and Chang (1977) and thus established quercetin as one of the most mutagenic flavonoids. (MacGregor & Jurd, 1978;Brown & Dietrich, 1979;Rueff et al, 1986). In vivo evaluation of quercetin showed its ability to act as a genotoxicant causing damage at the post meiotic stage of spermatogenesis in experimental rats.…”
Section: ) Effectsmechanism Of Actionmentioning
confidence: 99%
See 2 more Smart Citations